Apoptosis of rat ovarian granulosa cells by 2, 5‐hexanedione in vitro and its relevant gene expression. Issue 7 (15th February 2012) - Zhang, Wenchang; Huang, Lei; Kong, Cancan; Liu, Jin; Luo, Lingfeng; Huang, Huiling
ABSTRACT Although n‐hexane is toxic to the ovary, the related mechanism remains unknown. Apoptosis of rat ovarian granulosa cells is thought to be one of the important reasons for ovarian toxicity. Rat ovarian granulosa cells were exposed in vitro to different concentrations of 2, 5‐hexanedione (HD, a major metabolite of n‐hexane; 0, 20, 40 and 60 mmol l−1) to observe the apoptosis, and its relevant gene expression was investigated. It was found by MTT assay that different exposure doses and different exposure time could inhibit the viability of ovarian granulosa cells. After a 12 h exposure, we found the apoptosis rate of the ovarian granulosa cells increased notably with the increase of HD dose. The HD concentration of each exposure dose could inhibit the message RNA (mRNA) expression of both bcl‐2 and xiap, and increase the mRNA expression of fasl without any influence on that of bcl‐xl, while only an HD concentration of 40 mol l−1 could raise the mRNA expression of bax. Concentrations of HD of 40 and 60 mol l−1 could inhibit the protein expression of NF‐κB, but only an HD concentration of 60 mol l−1 could improve theactivation of NF‐κB. In summary, our results indicate that HD can induce the apoptosis of ovarian granulosa cell, and the occurrence of apoptosis is related to inhibition of protein expression of NF‐κB, activation of NF‐κB, upregulation of mRNA levels of fasl and bax, and downregulation of mRNA levels of xiap and bcl‐2. Copyright © 2012 John Wiley & Sons, Ltd.